Changes in methanogenic population size and CH4 production potential in response to crop phenology in tropical rice field - Dubey S.K.; Singh A.; Singh R.S.; Upadhyay S.N. (My University, 2025)
In order to understand the microbial ecology of CH4 production in rice field, population size of methanogens and pattern of CH4 production potential was determined during rice cultivation for two years (2009 and 2010). Population size varied between 4.88 × 105 and 13.98 × 105 copies g-1 dws during the entire study period and followed the trend: flowering > ripening > tillering > post-harvest > pre-plantation. Pattern of CH4 production potential was similar to the population size for different stages of the crop and followed the pseudo-first order kinetics, indicating a positive relationship between the population size of methanogens and CH4 production potential. An exponential relationship between the cumulative methane production potential and methanogenic population size was established. © 2012 Elsevier Ltd.